Correctional rehabilitation and psychological interventions in Singapore: practitioners' experiences in Singapore prison service - Cheng, Xiang Long; Ong, Gabriel (World Scientific Publishing, 2023)
Psychologists and correctional rehabilitation specialists in the Psychological and Correctional Rehabilitation Division of the Singapore Prison Service have been instrumental in designing and delivering the rehabilitation work with offenders. This book seeks to capture these experiences in the area of rehabilitation, and the anecdotal experiences working with different groups of offenders on the ground.It provides a first-hand look at the application of offender rehabilitation principles in practice. It also provides details on the experiences and challenges of working in a correctional context through the anecdotal sharing. To this end, the book aims to provide a practical and practitioner lens, overlaid with theoretical concepts, to the practice of correctional rehabilitation. While there have been experiences and insights documented, this will be the first book that documents the anecdotal experiences in Singapore Prison Service